Transient temperature heterogeneous distribution analysis in three-dimensional passive µDMFC - Yuan, Zhenyu; Zuo, Kaiyuan; Cao, Jiamu (International journal of heat and mass transfer, 2022)
•The temperature change before reaching a stable trend is simulated for the first time.•The non-uniform temperature distribution during cell start-up are analyzed.•A three-dimensional µDMFC model is established and verified by experiment. In this paper, the transient temperature heterogeneous distribution analysis in three-dimensional passive micro Direct Methanol Fuel Cell (µDMFC) is presented in detail. The metal-based µDMFC with the effective area of 1.0 cm2 is fabricated to verify the correctness of the model. By coupling the mass transport, momentum transport, electron-proton conduction and heat transfer mechanisms, the models of the whole cell and a single flow channel are established, and the non-uniform temperature changes in different stages of the cell are analyzed. Simulation results manifest that the temperature of collector and channel is in heterogeneous distribution state during the process of the fuel cell from starting work to reaching a stable trend. Due to the different fluids in the cathode and anode flow channels, the inside of flow channels also presents different heating trends. In addition, the temperature-increasing rate of each part of the cell after starting work is also simulated. The results can be used as a reference for the inner heterogeneous transfer and startup phase optimization of fuel cells. [Display omitted]